Auditing public finances in Morocco: The decisive role of the Court of Accounts - EL KAFSSAOUI , Achraf; TOUAB , Omar (Revue Internationale du Chercheur, 2024)
Morocco is embarking on a wide-ranging reform program, particularly in the area of project financing, with a particular focus on the public sector. In this context, public management is of paramount importance, particularly as regards the control of all financial operations linked to government departments, companies, and public establishments. The fundamental objective is to ensure the accountability of the various parties involved, particularly public accountants, and to detect any possible malfunctions in the management of public finances. To achieve this objective, the Court of Auditors and the Regional Audit Courts play a central role, in carrying out regular audits of public accounts. Their mission is to guarantee transparent and accountable financial management, thus ensuring the efficient use of public funds in Morocco. These institutions ensure that financial resources are managed by established standards, and highlight any irregularities or inefficiencies in the management of public funds. The control exercised by the Court of Auditors and the Cours Régionales de Comptes includes examining expenditure, revenue, and the management of public funds, as well as assessing compliance with the objectives set by the public authorities. This process involves in-depth investigations, regular audits, and detailed reports on the results of their interventions. The auditing of public finances in Morocco is of crucial importance in ensuring transparent, accountable, and efficient management of public resources. Thanks to the vigilant action of the Court of Auditors and the Cours Régionales de Comptes, the country can ensure that public funds are used appropriately and in line with established standards, thus contributing to the country’s economic and social development.